Assessing the Fitness-For-Purpose of strategic transport research in support of European transport policy - Tuominen, Anu; Leonardi, Jacques; Rizet, Christophe (European Journal of Transport and Infrastructure Research, 2008)
The transport policy environment is changing, because of increasing mobility of people and goods, world wide use of ICT, a rising importance of the knowledge economy, etc. Future methods for transport policy assessments will have to integrate these emerging trends, but above all, the new research knowledge produced needs to be taken better into use within the policy processes. To tackle the problem, the paper presents a generic fitness-for-purpose (FFP) Assessment method for research projects in support of transport policy. Based on the results of a case study, the paper argues that by linking a systematic FFP Analysis of transport research projects with researcher-civil servant network building, a method for accepting, elaborating and applying the produced European transport research knowledge can be provided. By doing this, the paper contributes to a more systematic and integrative assessment of transport research in policy support, and hopefully enhances the integration of transport research and policy making while at the same time, initiating a better based policy process. We see that FFP Assessments could offer an essential element for the policy relevant transport research knowledge production in the future.